Molecular and biochemical characterization of serine protease SmSP1 in Schistosoma mansoni - Opavský, David (Jihočeská univerzita, 2013)
SmSP1 is a chimerical serine protease consisted of three domains (cub, LDLa and trypsin-like) and found in Schistosoma mansoni. Its characterization was performed by molecular techniques such as PCR screen, qRT-PCR and RNA interference (RNAi) to gain information about expression profile, level expression and susceptibility to RNAi. Further, protein expression was carried out to gain an antigen for immunization and recombinant for biochemical studies. Results of PCR screen and qRT-PCR suggested possible function of SmSP1 in egg and adult stages but SmSP1 gene was not found susceptible to RNAi in NTS. Recombinant from E. coli was successfully used for immunization. Active recombinant was likely expressed in Pichia pastoris but expression conditions are unstable and expression optimization is necessary.
Molecular and biochemical characterization of serine protease SmSP1 in Schistosoma mansoni
Keywords: Schistosoma mansoni; serine protease; PCR screen; qRT-PCR; RNA interference; antigen; immunization; Schistosoma mansoni; serine protease; PCR screen; qRT-PCR; RNA interference; antigen; immunization